PEMETAAN ANCAMAN DAN KARAKTERISTIK KEBAKARAN HUTAN DAN LAHAN (KARHUTLA) PROVINSI LAMPUNG - Tohir, RIzki Kurnia; Pramatana, Fadlan (Fakultas Kehutanan Universitas Lancang Kuning, 2020)
Lampung Province has the threat of Forest and Land Fires (FLF) based on incident reports. There is a lack of data on how the threat level of the forest and land fires, so this research is important to do. This study aims to analyze the track record and potential for FLF incidents, to analyze the characteristics and level of the FLF threat. Threat mapping is done by weighting and scoring 11 variables. These variables are divided into natural factors and human factors. The results showed that the equation that gives a weighting of 90% to natural factors. The characteristics of FLF show that natural factors are sensitive factor for the occurrence of FLF in Lampung Province. Mapping of threats shows that the area of ​​low threat class is 244,811.96 ha (8%), medium threat class is 1207,716.15 ha (40%) and high threat class is 1,591,767.42 ha (52%). Three districts had the highest level of threat class, namely Way Kanan, Central Lampung, and East Lampung Districts. The results of the validation of field conditions are indicated by the results of this threat mapping, so that the results of this study can be used as material for consideration by policy makers.